Impor Pangan dan Perburuan Rente Perspektif Ekonomi Politik - Aziz SR, Abdul (Universitas Brawijaya, 2022)
The food import policies of the Joko-JK and Joko-Ma'ruf governments are often questioned and criticized by various groups. For at least three reasons. First, since the 2014 Presidential Election campaign, the Joko-JK pair declared “war” on food imports. There are promises that are often repeated –until when they are elected– not to import food such as rice, meat, salt, sugar, and others. Second, domestic potential can actually be optimized to meet food needs. The government itself provides a written commitment to self-sufficiency in food. Third, food import policies are often ineffective, because apart from not making prices stable, the elites are also more interested in them. Food imports that flowed heavily from the Joko-JK era to the Joko-Ma'ruf period lacked an objective (economic) reason, but rather because of the interest of rent-seeking by rent-seekers. This policy actually reinforces extractive economic practices, rather than efforts to improve the welfare of the societies.